2022
DOI: 10.3389/fmicb.2022.816622
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Starved Yeast Cells in IF1 Levels Suggests the Role of This Protein in vivo

Abstract: In mitochondria, a small protein IF1 suppresses the hydrolytic activity of ATP synthase and presumably prevents excessive ATP hydrolysis under conditions of energy deprivation. In yeast Saccharomyces cerevisiae, IF1 homologs are encoded by two paralogous genes: INH1 and STF1. INH1 expression is known to aggravate the deleterious effects of mitochondrial DNA (mtDNA) depletion. Surprisingly, no beneficial effects of INH1 and STF1 were documented for yeast so far, and the functions of INH1 and STF1 in wild type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this regard, both the mutual action of inhibitory proteins and ADP(Mg 2+ ) [ 59 , 91 , 92 ] and their independent action on the F 1 ∙F o regulation are considered [ 50 ], but no consensus has been reached so far. Using compounds with a pronounced activating effect on the latent F 1 ∙F o hydrolytic activity, it was concluded that εCTD- and ADP(Mg 2+ )-induced inhibition are mutually exclusive for the membrane-bound Ec F 1 ·F o [ 50 ].…”
Section: Reversibility Of F 1 F O ...mentioning
confidence: 99%
“…In this regard, both the mutual action of inhibitory proteins and ADP(Mg 2+ ) [ 59 , 91 , 92 ] and their independent action on the F 1 ∙F o regulation are considered [ 50 ], but no consensus has been reached so far. Using compounds with a pronounced activating effect on the latent F 1 ∙F o hydrolytic activity, it was concluded that εCTD- and ADP(Mg 2+ )-induced inhibition are mutually exclusive for the membrane-bound Ec F 1 ·F o [ 50 ].…”
Section: Reversibility Of F 1 F O ...mentioning
confidence: 99%
“…We have also recently demonstrated that post-diauxic yeast cells form two subpopulations characterised by high and low concentrations of mitochondrial ATP-ase inhibitor proteins (Inh1p and Stf1p). Cells with an elevated inhibitor level recovered more rapidly from the stationary phase than their low-level counterparts, at the same time a high concentration of the inhibitor proteins was deleterious under the conditions of mitochondrial dysfunction ( Galkina et al, 2022 ). These examples show that cell culture phenotypic heterogeneity can be detrimental or adaptive depending on which specific phenotypic properties are considered.…”
Section: Main Textmentioning
confidence: 99%